Cmentarzysko ludności kultury pucharów lejkowatych w Marianowie, pow. koniński, stan. 17 - Gorczyca, Krzysztof (Folia Praehistorica Posnaniensia, 2015)
The cemetery in Marianowo is the first non-megalithic burial site of the Funnel Beaker culture (hereinafter referred to as TRB from German Trichterbecherkultur), which has been recorded in eastern Wielkopolska. It is also the first one where biritual funeral rites have been adopted. Despite the poor evidence, it might be generally dated to the Classic Wiórek phase (III), and even to sub-phase IIIC of TRB. All six unearthed burials were of children, and the question of the reason why one of them was cremated provides a wide range of interpretative alternatives.